Pancasila dan agama sebagai pilar etika sosial masyarakat Indonesia - Mufarrohah, Mufarrohah (Maliki Interdisciplinary Journal, 2026)
This abstract examines the role of Pancasila and religion as the two fundamental pillars shaping Indonesia’s social ethics amidst globalization and rapid socio-cultural transformation. As the philosophical foundation of the state, Pancasila embodies values rooted in local culture, tradition, and religious teachings, forming a moral framework that guides social behavior. Religion further strengthens ethical attitudes such as tolerance, respect, empathy, and social harmony. The journals analyzed indicate that character education in Social Studies (IPS) plays a strategic role in internalizing these values through teacher modeling, habituation, and contextual learning activities. Globalization poses challenges such as rising individualism and moral degradation; therefore, character education must be adaptive and responsive to maintain national identity and moral integrity. This study concludes that Pancasila and religion function as complementary forces in shaping a civilized, harmonious, and just society and must be systematically integrated into the educational process to effectively respond to contemporary challenges.